DAMPAK AJANG FASHION SHOW YANG MENGGUNAKAN ZEBRA CROSS - Nur Harifa; H. R.Adianto Mardijono (Gapenas Publisher, 2023)
Laws are made to function as social control. One of them is in the laws of our country, such as the Road Traffic and Transportation Law (LLAJ Law). This law has rules for roads and transportation as well as rules for traffic. Zebra Crosses are made across the middle of the road to notify motorists that there is a lane for pedestrians to cross. There are fashion shows that use zebra crossing as a means of displaying trends and styles of dress, such as the famous Paris Fashion Week, where models sway in their signature clothes when crossing the street. Law number 22 of 2009 concerning Road Traffic and Transportation stipulates that the Zebra Cross function is none other than a pedestrian crossing. Article 131 of the law explains that zebra crossing is one of the facilities rights provided to pedestrians other than sidewalks. Further explained in Article 132, pedestrians are required to use a zebra crossing when they want to cross the road